Optically operated second order optical effects in some substituted 4-(5-nitro-1, 3-benzoxazol-2-yl)aniline chromophores. (June 2017) - Szlachcic, P.; Fedorchuk, A.A.; Danel, A.; Jarosz, B.; El Naggar, A.M.; Albassam, A.A.; Wojciechowski, A.; Gondek, E.; Uchacz, T.; Stadnicka, K.; Lakshminarayana, G.; Kityk, I.V.
Abstract: In this work, we report on second order nonlinear optical (NLO) susceptibilities of some substituted 4-(5-nitro-1, 3-benzoxazol-2-yl)aniline chromophores that were embedded into photopolymer matrices. Depending on the photo-induced nitrogen laser (wavelength 371 nm) power density of photo-solidification we found an optimal photo-solidification parameter to achieve maximum second harmonic generation (SHG). The influence of the π-conjugated bonds on the output second order susceptibility and HOMO-LUMO level positions is analysed. The performed experiments are compared with the theoretically calculated microscopic hyper-polarizabilities obtained within the B3LYP DFT approach. The possible operation by the output SHG efficiency versus the photoinduced laser power density is presented. The role of the intra-molecular and surrounding polymers in the observed nonlinear optical behaviour is explored. Graphical abstract: Highlights: Second order nonlinear optical susceptibilities of organic chromophores/photopolymer matrices were studied. Microscopic hyper-polarizabilities were obtained within the B3LYP DFT approach. SHG efficiency versus the photoinduced laser power density is presented. DFT simulations confirm the donor–acceptor charge transfer in the observed output second-order efficiencies. The effects are crucially dependent on the photo-illumination time.